Demographic and Dietary Determinants of the Association between Dietary Fiber Intake and Obesity in Japanese Adults with Type 2 Diabetes: A Cross-Sectional Study (JDDM 78) - Efrem d'Ávila Ferreira; Mariko Hatta; Laymon Khin; Izumi Ikeda; Mizuki Takeuchi; Yasunaga Takeda; Sakiko Yoshizawa Morikawa; Chika Horikawa; Noriko Kato; Hiroshi Maegawa; Kazuya Fujihara; Hirohito Sone (Public Health Nutrition)
Abstract